Clinical Utility of Semistructured Interview and Scales to Assess Withdrawal Syndromes With Dose Reduction or Discontinuation of Selective Serotonin Reuptake Inhibitors or Serotonin Norepinephrine Reuptake Inhibitors. Issue 1 (January 2022) - Cosci, Fiammetta; Romanazzo, Sara; Mansueto, Giovanni; Rontani, Petra; Levitan, Michelle N.; Halkjœr-Lassen, Roseane D.; Quagliato, Laiana A.; Nakamura, Tomoyuki; Uematsu, Ken; Nardi, Antonio E.; Oe, Misari; Chouinard, Virginie-Anne; et al.
Abstract: Background: Withdrawal syndromes can occur after dose reduction or discontinuation of selective serotonin reuptake inhibitors (SSRIs) or serotonin-norepinephrine reuptake inhibitors (SNRIs). Few measurement instruments are available to assess them: Diagnostic Clinical Interview for Drug Withdrawal 1–New Symptoms of SSRI and SNRI (DID-W1) and Discontinuation Emergent Signs and Symptoms (DESS) checklist. We assessed their interrater reliability, verified the percent agreement between the two, and tested DESS sensitivity and specificity on the basis of the diagnoses formulated via the DID-W1. Methods: One-hundred thirty-four subjects who referred for withdrawal at 3 outpatient facilities were enrolled and assessed via the DESS and the DID-W1. Percent agreement and Cohen κ were calculated to measure DID-W1 and DESS interrater reliability, as well as the agreement between DID-W1 and DESS items. Sensitivity and specificity of DESS were derived from the identification of true-positive, false-negative, true-negative, and false-positive on the DID-W1. Results: Both tools showed excellent interrater reliability (DID-W1 Cohen κ = 0.958; DESS Cohen κ = 0.81–1). The degree of agreement between DID-W1 and DESS items was poor or fair (Cohen κ < 0.40) for some items and moderate (Cohen κ = 0.41–0.60) for others. Sensitivity and specificity of DESS were 0.937 (true-positive = 60, false-negative = 4) and 0.285 (true-negative = 20, false-positive = 50), respectively. Conclusions: DID-W1 was a reliable method to identify and diagnose withdrawal syndromes. The DESS checklist showed to be a useful tool for detecting withdrawal SSRI/SNRI symptoms when the aim is to achieve high sensitivity to identify true positives.